Geldanamycin, a Naturally Occurring Inhibitor of Hsp90 and a Lead Compound for Medicinal Chemistry - Kitson, Russell R A; Kitsonová, Dominika; Siegel, David; Ross, David; Moody, Christopher J (Journal of medicinal chemistry, 2024)
Geldanamycin remains a driver in the medicinal chemistry of heat shock protein 90 (Hsp90) inhibition, even half a century after its original isolation from nature. This Perspective focuses on the properties of the benzoquinone ring of the natural product that enable a range of functionalization reactions to take place. Therefore, inherent reactivity at C-17, where the methoxy group serves as a vinylogous ester, and at C-19 that demonstrates nucleophilic, enamide-type character toward electrophiles, and also as a conjugate acceptor to react with nucleophiles, has facilitated the synthesis of semisynthetic derivatives. Thus, a range of C-17-substituted amine derivatives has been investigated in oncology applications, with a number of compounds in this series reaching clinical trials. In contrast, the 19-position of geldanamycin has received less attention, although 19-substituted derivatives offer promise with markedly reduced toxicity compared to geldanamycin itself, while retaining Hsp90 inhibitory activity albeit with diminished potency in cellular studies.
Keywords: Structure-Activity Relationship; farmaceutická chemie; vztahy mezi strukturou a aktivitou; HSP90 Heat-Shock Proteins; Lactams, Macrocyclic; Animals; lidé; Chemistry, Pharmaceutical; protinádorové látky; benzochinony; Humans; zvířata; Antineoplastic Agents; proteiny tepelného šoku HSP90; Benzoquinones; makrocyklické laktamy